Rapid prototyping in Malaysia - Wan Yusoff, Wan Mohd Yusmawiza; Md Zain, Mohd Izzuan; Kamasan, Muhammad Asrul; Nor Aman, Zuraida (2009)
Rapid prototyping (RP) has become one major play role particularly in the area of product development by providing a quick solid view on parts or products before it can be further into productions. Thus, the purpose of this study is to determine the growth of rapid prototyping’s populations and its’ potential in malaysia. Regarding to this matter, the methodology of this study is conducted through surveys of all the possible rapid prototyping (RP) users in Malaysia. The result of the survey shows the typical reluctant development of the rapid prototyping within the aspect of usage and population. Somehow it also can be concluded that a positive potential for the both aspects as the educational and researches purposes superior the production industries. Therefore, the exposure of this study contributes to the realization for the investment in this advanced manufacturing technology field.